Smart Wearable Devices for Monitoring Child Behavioral Health - Mikkel Arvid Larsen; Kristian Ole Magnus (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2024)
Behavioral health disorders in children, such as anxiety and depression, are on the rise, and early detection is crucial for effective intervention. This paper explores the use of smart wearable devices to monitor behavioral health in children. By tracking physiological signals such as heart rate, sleep patterns, and stress levels, these devices provide real-time data that can help caregivers and healthcare professionals identify early signs of behavioral health issues and initiate timely treatment.